IMPLEMENTASI PEMBELAJARAN BERBASIS BAHAN BEKAS DALAM MENINGKATKAN KREATIVITAS DAN MOTIVASI BELAJAR DI TK BINA ANAPRASA CEMPAKA III - Yami, Nuryami; Kartika Fajriyani; Lina Revilla Malik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the integration of recycled-material-based learning within the Early Childhood Education curriculum at TK Bina Anaprasa Cempaka III. The focus is on how this approach is implemented to support children’s learning activeness and learning motivation in classroom activities. A descriptive qualitative method was employed, involving 20 children aged 5–6 years and one classroom teacher. Data were collected through passive participatory observation, semi-structured interviews, and documentation. The analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. This study is expected to provide insights into the use of recycled materials as learning media to create more engaging, interactive, and meaningful learning experiences, while encouraging children’s active participation in the learning process.